If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -2) + 4x = -27 Reorder the terms: 3(-2 + x) + 4x = -27 (-2 * 3 + x * 3) + 4x = -27 (-6 + 3x) + 4x = -27 Combine like terms: 3x + 4x = 7x -6 + 7x = -27 Solving -6 + 7x = -27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 7x = -27 + 6 Combine like terms: -6 + 6 = 0 0 + 7x = -27 + 6 7x = -27 + 6 Combine like terms: -27 + 6 = -21 7x = -21 Divide each side by '7'. x = -3 Simplifying x = -3
| u^5-13u^3+36u=0 | | 5b+4b=6b-2 | | 5(x-6)+4=7(x+2)-12 | | 4v^2+4v-168=0 | | 58.5=3.5x | | 9x^3+25x-30x^2=0 | | 8-3x=5(x+8) | | 13=x-25 | | -8+x=7x-68 | | 2-5(x-3)=8 | | 16=3x-4 | | 9t+1=4t-9 | | 2x-4x=4x-10 | | x-20=(-8) | | -3=12y-5*2y-7 | | 3g+1.2g=14 | | 2x-12y=0 | | 5m+6=-4 | | 2x+5=-50-3x | | 4p^2-44p+121=0 | | 13k+5=k+-7 | | x^2+3x=153 | | -24x-53=39-x | | 10x^3-15x^2=0 | | 43=16*4g | | 4x^3-x^2=5x | | 5a=-60 | | x-7=-53 | | 3y-12=6 | | -12r=-36 | | x-31=-5 | | -5-5x=5 |